Stereotype accommodation: a socio-cognitive perspective on migrants’ cultural adaptation - Stanciu, A.; Vauclair, C.-M. (Journal of Cross-Cultural Psychology, 2018)
Cognitive heuristics, or people’s stereotypes, are central to human interaction. Yet, the literature has been concerned with inter-ethnic stereotypes held by migrants and therefore has insufficiently addressed what might happen to individuals’ cognitive heuristics in the process of acculturating to host cultures. The authors discuss this gap in the literature by drawing on the culture learning perspective and work on cultural adaptation to examine migrants’ cognitive cultural adaptation. The concept of stereotype accommodation is introduced as a cognitive process whereby migrants incorporate the stereotype-relevant information learned in their host cultures into their preexisting stereotypes. Furthermore, a framework is presented for how cross-cultural differences, learning opportunities, individual differences, and cognitive resources might contribute to stereotype accommodation. The conclusion of this analysis is that, like any other individuals, migrants hold cognitive heuristics about varying groups in society and, moreover, these can be influenced and potentially modified by the mental short-cuts that are relevant in their host cultures.